Development of Community-Based Tourism (CBT) at the Rammang-Rammang Tourist Attraction, Maros Regency: A Triple Bottom Line Approach: Assessing Sustainability Impacts on Environment, Economy, and Communit - D, Sabran Laori (Quantitative Economics and Management Studies, 2025)
Rammang-Rammang is one of the world’s largest karst areas, located in Maros Regency, South Sulawesi, and part of the Maros-Pangkep UNESCO Global Geopark. The area has strong potential as a natural and cultural attraction but faces challenges such as limited infrastructure, inadequate sanitation, and environmental threats from growing tourism activities. This study explores how Community-Based Tourism (CBT) strategies can be implemented, the role of government in destination management, and how SWOT, IFAS, and EFAS analyses help assess internal and external conditions. Using a descriptive qualitative method, data were collected through observation, in-depth interviews, and documentation. Informants included the head of the tourism awareness group, attraction managers, boat operators, and local residents. Data analysis used SWOT supported by strategic matrices, along with IFAS and EFAS. Results show that tourism development prioritizes community empowerment, human resource capacity, cultural identity, and environmental preservation based on the Triple Bottom Line. The IFAS score of 2.55 indicates that strengths outweigh weaknesses, especially natural beauty, community involvement, and government support. The EFAS score of 2.65 shows opportunities exceed threats, such as UNESCO status and the rise of nature-based tourism. Overall, CBT-based strategies supported by the government and community can promote sustainable economic, social, and environmental development.